Dollarization and the "unbundling" of globalization in sub-Saharan Africa - Kazeem Bello Ajide; Ibrahim Dolapo Raheem; Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
This study contributes to the dollarization literature by expanding its determinants to account for different dimensions of globalization, using the widely employed KOF index of globalization. Specifically, globalization is "unbundled" into three different layers namely : economic, social and political dimensions. The study focuses on 25 sub-Saharan African (SSA) countries for the period 2001-2012.Using the Tobit regression approach, the following findings are established. First, from both economic and statis tical relevance, the social and political dimensions of globalization constitute the key dollarization amplifiers, while the explanatory power of the economic component is weak er on dollarization. Second, consistent with the theoretical underpinnings, macroeconomic instabilities (such as inflation and exchange rate volatilities) have the positive expected signs. Third, the positive association between the accumulation of international reserves and dollarization is also apparent. Policy implications are discussed.
Keywords: E41; F41; C21; 330; Dollarization; Globalization; sub-Saharan Africa; Tobit regression